Genus Gentiana: A review on phytochemistry, pharmacology and molecular mechanism. (10th January 2021) - Jiang, Min; Cui, Ben-Wen; Wu, Yan-Ling; Nan, Ji-Xing; Lian, Li-Hua
Abstract: Ethnopharmacological relevance: As the largest genus of Gentianaceae family, the Gentiana genus harbors over 400 species, widely distributed in the alpine areas of temperate regions worldwide. Plants from Gentiana genus are traditionally used to treat a wide variety of diseases including easing pain dispelling rheumatism, and treating liver jaundice, chronic pharyngitis and arthritis in China since ancient times. In this review, a systematic and constructive overview of the traditional uses, phytochemistry, molecular mechanisms, toxicology and pharmacological activities of the researched species of genus Gentiana is provided. Materials and methods: The used information in this review is based on various databases (PubMed, Science Direct, Wiley online library, Wanfang Data, Web of Science) through a search using the keyword " Gentiana " in the period of 1981–2019. Besides, other ethnopharmacological information was acquired from Chinese herbal classic books and Chinese pharmacopoeia 2015 edition. Results: The plants from Gentiana genus have a long tradition of various medicinal uses in Europe and Asia. Phytochemical studies showed that the main bioactive components isolated from this genus includes iridoids xanthones and flavonoids. These compounds and extracts isolated from this genus show a wide range of protective activities including hepatic protection, gastrointestinal protection, cardiovascular protection, immunomodulation, joint protection, pulmonary protection, bone protection and reproductive protection. Molecular mechanism studies also indicated several potential therapeutic targets in the treatment of certain diseases by plants from this genus. Besides, natural products from this plant show no significant animal toxicity, cytotoxicity or genotoxicity. Conclusion: This review summarized the traditional medicinal uses, phytochemistry, pharmacology, toxicology and molecular mechanism of genus Gentiana, providing references and research tendency for plant-based drug development and further clinical studies. Graphical abstract: Image 1